On value and valuation - Frow, John, 1948- author. Link
1 online resource
Keywords: On Value and Valuation asks whether the category of economic value remains theoretically viable, how value is formed, and how it should be understood. It explores the interlinkages between economic value and social and cultural values.On the one hand, the book draws on anthropological and sociological accounts of the evaluative frameworks within which things take on their social meanings; on the other, it explores and critiques the Marxist account of the formation of value in capitalist production. Its aim is to reconcile these two conceptions, and it does so by arguing that economic value is not a property of goods and services but is formed in specific institutions of valuation. It analyses new sources of value generated in markets in derivatives, in carbon credits and ecosystem services, in expert systems, and in new digital entities and seeks to deepen our understanding of value as a force driven by a web of social relations of accumulation that channel power and coercion.This book will be of interest to students of heterodox economics and Marxist theory, as well as to those with a wider concern with questions of social and economic value.